Fast Determination of Auramine O in Food by Adsorptive Stripping Voltammetry - Thuong Nguyen Thi Kim; Thi Thu Bui; Anh Tuan Pham; Van Thang Duong; Thi Huong Giang Le (Journal of Analytical Methods in Chemistry, 2019)
The electrochemical behaviour of auramine O on the hanging mercury drop electrode has been investigated by cyclic and square wave voltammetry method. Reduction peak of auramine O was irreversible and adsorptive on the hanging mercury drop electrode. The optimal conditions were chosen to be Briton–Robinson buffer pH 9.0, accumulation potential −0.5 V vs. Ag/AgCl/KCl, accumulation time 60 s, pulse amplitude 250 mV·s−1, and frequency 50 Hz. At the optimum experimental conditions, the peak of the target analyte was sharp and asymmetric. The linearity of the peak current depending on the concentration ranged from 4.0 × 10−8 to 6.4 × 10−7 mol L−1. The limit of detection and limit of quantitation were 2.46 × 10−8 mol L−1 and 8.21 × 10−8 mol L−1, respectively. The recovery and relative standard deviation were 94.9% and 2.0% (n = 5). The developed method was successfully applied to determine auramine O in chicken samples with an appropriate sample preparation.